2019
DOI: 10.1111/jocn.14742
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of the Positive Sexuality Scale for female adults

Abstract: Aim and objectives To develop and initially validate the Positive Sexuality Scale (PSS) to assess adult female‐positive sexuality. Background While traditional approaches focus on negative sexual experiences and sexual dysfunctions, within the positive psychology framework positive sexuality is a subjective experience of happiness and fulfilment with one’s sexual expression, which contributes to well‐being. No measure exists that specifically measures adult female‐positive sexuality and can be confidently used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…To our knowledge, no previous studies have related age and relationship length with positive sexuality. The only exception is the original validation study of the PSS [19]. That study reported slightly higher positive sexuality levels in younger women than in older ones, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To our knowledge, no previous studies have related age and relationship length with positive sexuality. The only exception is the original validation study of the PSS [19]. That study reported slightly higher positive sexuality levels in younger women than in older ones, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Dyadic invariance testing is especially critical in the field of sexuality, as men and women might hold different conceptualizations of sexuality-related dimensions [4]. We tested the dyadic invariance of the Positive Sexuality Scale (PSS), a brief one-factor measure of positive sexuality developed within the sex-positive framework [19]. Our findings supported full configural, metric, and scalar invariance, and partial strict invariance, indicating that the PSS works in the same way for both members of Chilean heterosexual couples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, individuals with better physical health and healthier lifestyles report higher sexual satisfaction, sexual pleasure, and sexual desire ( Flynn et al, 2016 ; Mollaioli et al, 2020 ; Gianotten et al, 2021 ). Furthermore, positive sexuality indicators such as sexual satisfaction and sexual wellbeing are positively associated with psychological well-being and self-esteem ( Casu, 2019 ; Leavitt et al, 2019 ; Shaughnessy et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%